Additive Manufacturing of Biomaterials − The Evolution of Rapid Prototyping. Issue 2 (3rd January 2019) - Touri, Maria; Kabirian, Fatemeh; Saadati, Mahdi; Ramakrishna, Seeram; Mozafari, Masoud
Abstract : Biomaterials rapid prototyping (RP), recently known as additive manufacturing (AM), has appeared as a revolutionary technology, promising to transform research into medical therapeutics. RP is a layer by layer manufacturing process which directly translates computer data such as Computer Aided Design (CAD), Computer Tomography (CT), and Magnetic Resonance Imaging (MRI) into three‐dimensional (3D) objects. RP technologies play a significant role in biomedical industry such as anatomical models for surgery training/planning, rehabilitation, dentistry, customized implants, drug delivery devices, tissue engineering, and organ printing. The integration of biomaterials and rapid prototyping technologies is an exciting route in developing biomaterial implants for the past decade. This review describes and classifies the RP systems into three categories of liquid‐based, solid‐based, and powder‐based according to the initial form of their feed materials. Then, discusses possible benefits, drawbacks, and applications of each process in the field of biomaterials science and engineering. Abstract : Additive manufacturing has recently appeared as a revolutionary technology in biomedical engineering. It plays a critical role in biomedical industry such as anatomical models for surgery training/planning, rehabilitation, dentistry, customized implants, drug delivery devices, tissue engineering, and organ printing. This comprehensive review summarizes all the possible categories of liquid‐based, solid‐based, and powder‐based systems for additive manufacturing of biomaterials.